The sanitary plumbing of a modern house - Teagarden, Maude E. (My University, 1908)
Introduction: The busy housewife hails with delight at any sensible labor-saving device. Of all the modern arrangements, the house plumbing system is undoubtedly the most convenient. It supplies all the water necessary for domestic and other purposes and removes quickly all fluid and semi-fluid waste with no effort whatever on the part of the occupants of the house.
Citation: Teagarden, Maude E. The sanitary plumbing of a modern house. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Plumbing; Architecture; Water; Sewage; Graduating theses; Senior theses; Theses